Fermentasi Limbah Kepala Ikan Gabus (Channa striata) dengan Batang Pisang Menjadi Pupuk Organik Cair - Faqih Sembada Wijayatin; Farhah Kamilatun Nuha; Retno Dewati (Jurnal Serambi Engineering, 2024)
The fish processing industry often produces large amounts of waste. The abundance of these wastes can be used as liquid organic fertiliser so that it would not become pollution. This research will use cork fish head waste which had 17.72% C-organic; 0.189% nitrogen; 0.126% phosphorus; and 0.041 potassium with banana stalks as additional material which had 15.68% C-organic; 1.35% phosphorus; 2.13% potassium; 0.02 nitrogen to be used as liquid organic fertilizer. This research was carried out in 3 stages. The first was the preparation of the main ingredients, followed by the preparation of the bioactivator solution and then the fermentation process. The fermentation process was carried out in 5 different containers, each containing 10, 20, 30, 40 and 50 ml of bioactivator solution. Samples were taken on days 7, 10, 13, 16 and 19 to test for nutrient content. The results showed that the liquid organic fertiliser from cork fish head and banana stem with the best results and meeting the SNI standards was obtained in samples with 30 ml of EM4 added to it and fermented for 10 days, with a C/N ratio of 12.187% and total macro-nutrients (N + P2O8 + K2O) of 5.887%.